Cannabinoids facilitate the swallowing reflex elicited by the superior laryngeal nerve stimulation in rats - Zakir, H.M. (Public Library of Science, 2012)

(untitled)
Cannabinoids have been reported to be involved in affecting various biological functions through binding with cannabinoid receptors type 1 (CB1) and 2 (CB2). The present study was designed to investigate whether swallowing, an essential component of feeding behavior, is modulated after the administration of cannabinoid. The swallowing reflex evoked by the repetitive electrical stimulation of the superior laryngeal nerve in rats was recorded before and after the administration of the cannabinoid receptor agonist, WIN 55-212-2 (WIN), with or without CB1 or CB2 antagonist. The onset latency of the first swallow and the time intervals between swallows were analyzed. The onset latency and the intervals between swallows were shorter after the intravenous administration of WIN, and the strength of effect of WIN was dose-dependent. Although the intravenous administration of CB1 antagonist prior to intravenous administration of WIN blocked the effect of WIN, the administration of CB2 antagonist did not block the effect of WIN. The microinjection of the CB1 receptor antagonist directly into the nucleus tractus solitarius (NTS) prior to intravenous administration of WIN also blocked the effect of WIN. Immunofluorescence histochemistry was conducted to assess the co-localization of CB1 receptor immunoreactivity to glutamic acid decarboxylase 67 (GAD67) or glutamate in the NTS. CB1 receptor was co-localized more with GAD67 than glutamate in the NTS. These findings suggest that cannabinoids facilitate the swallowing reflex via CB1 receptors. Cannabinoids may attenuate the tonic inhibitory effect of GABA (gamma-aminobuteric acid) neurons in the central pattern generator for swallowing.